Possible Cytoprotective Potential of Ruthenium Red in Evaluation of the Rapid Apoptotic Model Induced by H2O2 - Bayram, Recep; Zeynep Yavuz, Muhsine; Duzenli, Selma; Gepdiremen, Akcahan (Asian Journal of Chemistry, 2010)
In the present paper, hydrogen peroxide (H2O2) induced an apoptotic process in 1 h and over the doses of 10 mM, while cisplatin did not, in cortical neuronal homogenates of rats. It was proved in DNA fragmentation, MTT and WST-1 assays. Especially, according to WST-1 assay results, apoptotic effect was decided to be very obvious in all tests in the doses of 20 mM of the rapid model of apoptosis of H2O2. Ruthenium red, as a mitochondrial Ca2+ modulator, was tested alone and co-application with H2O2. Without H2O2, at low doses of it, ruthenium red seems to have a slight viability inducing effect in respect to controls in MTT and WST-1, despite that this effect was not observed clearly in DNA fragmentation test. Another point is that the highest dose of ruthenium red (10-4 M), induces apoptosis, even stronger than the 20 mM H2O2, controversy to the general believing.